2010
DOI: 10.4049/jimmunol.1001006
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Motifs but Overlapping Binding Repertoires of Six HLA-DQ Molecules Frequently Expressed in the Worldwide Human Population

Abstract: Knowledge of the binding repertoires and specificities of HLA-DQ molecules is somewhat limited and contradictory, partly because of the scarcity of reports addressing some of the most common molecules and possibly because of the diversity of the techniques used. In this paper, we report the development of high-throughput binding assays for the six most common DQ molecules in the general worldwide population. Using comprehensive panels of single substitution analogs of specific ligands, we derived detailed bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 87 publications
(149 reference statements)
9
95
1
4
Order By: Relevance
“…[35][36][37] The HLA-peptide binding studies revealed that the selfpeptides derived from these autoantigens bound promiscuously to the susceptible, neutral and protective DR and DQ allele products, [38][39][40] which may reflect the facts that the peptide-binding spectrum of DR and DQ allele products partially overlaps across alleles. 41,42 It has remained unknown whether the HLA associations with T1D can be explained by the selective presentation of certain pancreatic self-peptides on the susceptible HLA allele products. Potential contributions of other functional variations among the alleles, such as the promoter activity 43 and the dependency of HLA proteins to invariant chain and HLA-DM, [44][45][46] to T1D risk have also been reported.…”
Section: Associations Between Hla Class II and T1dmentioning
confidence: 99%
“…[35][36][37] The HLA-peptide binding studies revealed that the selfpeptides derived from these autoantigens bound promiscuously to the susceptible, neutral and protective DR and DQ allele products, [38][39][40] which may reflect the facts that the peptide-binding spectrum of DR and DQ allele products partially overlaps across alleles. 41,42 It has remained unknown whether the HLA associations with T1D can be explained by the selective presentation of certain pancreatic self-peptides on the susceptible HLA allele products. Potential contributions of other functional variations among the alleles, such as the promoter activity 43 and the dependency of HLA proteins to invariant chain and HLA-DM, [44][45][46] to T1D risk have also been reported.…”
Section: Associations Between Hla Class II and T1dmentioning
confidence: 99%
“…FVIII 508-527 binding to DRB1*01:01 and DRB1*10:01 was tested experimentally yielding 50% inhibitory concentration values .20 mM, which is considerably higher than the 1000 nM affinity threshold defined for MHCII binding, [47][48][49] whereas FVIII 2194-2213 bound to DRB1*01:01 with an 50% inhibitory concentration of 0.33 mM (supplemental Figure 3). The ProPred and Immune Epitope Database programs predicted that 28 and 15 core FVIII sequences, respectively, could bind DRB1*01:01 (supplemental Tables 2-3).…”
Section: Epitope Mappingmentioning
confidence: 99%
“…Specific HLA class II alleles, including DQB1⁄0201 and DQB1⁄0602, may affect the risk of human diseases due to the presence of HLA-DQ-restricted immune responses. 13,14 To our knowledge, this is the first report discussing HLA class II DQB1 typing in patients with KLS in a Taiwanese population. An immunoresponsive HLA-DQB1 allele, DQB1⁄0602, is detected in significant quantities in patients with KLS, which is helpful in identifying the genomic susceptibility of KLS and determining immunospecific targeted therapies for patients with this genetic disorder.…”
Section: Discussionmentioning
confidence: 92%